A robust five-unknowns higher-order deformation theory optimized via machine learning for functionally graded plates - (:unkn) unknown (Taylor & Francis, 2024)
This article presents a new kind of higher-order deformation theory, called Parametric Higher-order Deformation Theory (PHDT), for the static analysis of functionally graded plates (FGPs). The novelty of the PHDT is the use of strain shape functions that...
Keywords: Aprendizaje automático; Placas funcionalmente gradadas